A survey on sms mobile marketing : antecedents to permission on young consumers - Teo, Huey Lian (Universiti Malaysia Sarawak, (UNIMAS), 2010)
The objective of this study is to exam the significance relationship between the four antecedent factors of mobile market experience, personal trust, perceived control, institutional trust, and interaction gender that affects young consumers' willingness to give permission in receiving SMS advertising.